Formation of the structure and properties of the near-surface layer in alloys of the Ti–6Al–4V–H system under irradiation with a pulsed electron beam; Russian Physics Journal; Vol. 66, No. 2 - Grabovskaya G. P. Galina Petrovna; Stepanova E. N. Ekaterina Nikolaevna; Zabudchenko O. V. Olga Vyacheslavovna; Mishin I. P. Ivan Petrovich (2023, 2023)
Title screen